2019
DOI: 10.2147/idr.s228026
|View full text |Cite
|
Sign up to set email alerts
|

<p><em>Helicobacter pylori</em>, Endoscopic, And Histologic Features Among Kidney Transplant Candidates In Southern Iran</p>

Abstract: BackgroundThe risks of gastrointestinal disorders and cancer are higher in chronic kidney disease (CKD) patients than the general population. There are only a few published reports on the association of helicobacter pylori (H. pylori) infection, endoscopic findings, and histology in these patients. This study was designed to address these controversial topics among kidney transplant candidates as the first study in southern Iran.Patients and methodsIn this cross-sectional study, patients undergoing renal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
1
8
0
1
Order By: Relevance
“…58 In a cross-sectional study including 293 Iranian patients undergoing kidney transplant, 50% of them were H pylori positive by gastric biopsy testing. 59 Interestingly, H pylori infection could be a potential risk factor for renal damage in patients with peptic ulcer, as a positive association between this bacterium and altered albumin-to-creatinine ratio (P = .025) was found, and a significant decrease of the latter occurred after H pylori eradication (P < .01). 60 epitope spreading, and polyclonal activation.…”
Section: K Idne Y D Is E a S E Smentioning
confidence: 96%
See 1 more Smart Citation
“…58 In a cross-sectional study including 293 Iranian patients undergoing kidney transplant, 50% of them were H pylori positive by gastric biopsy testing. 59 Interestingly, H pylori infection could be a potential risk factor for renal damage in patients with peptic ulcer, as a positive association between this bacterium and altered albumin-to-creatinine ratio (P = .025) was found, and a significant decrease of the latter occurred after H pylori eradication (P < .01). 60 epitope spreading, and polyclonal activation.…”
Section: K Idne Y D Is E a S E Smentioning
confidence: 96%
“…A systematic review with meta‐analysis, including 47 studies, recently reported a prevalence of H pylori infection in 48% of patients with chronic kidney disease (CKD) compared to 59% of healthy controls, with an OR of 0.64 (95% CI, 0.52‐0.79) 58 . In a cross‐sectional study including 293 Iranian patients undergoing kidney transplant, 50% of them were H pylori positive by gastric biopsy testing 59 . Interestingly, H pylori infection could be a potential risk factor for renal damage in patients with peptic ulcer, as a positive association between this bacterium and altered albumin‐to‐creatinine ratio ( P = .025) was found, and a significant decrease of the latter occurred after H pylori eradication ( P < .01) 60 …”
Section: Kidney Diseasesmentioning
confidence: 99%
“…Although evidence demonstrating an association between H. pylori infection and renal disease remain unknown. About 25% -75% of chronic kidney disease (CKD) patients suffer from multiple gastrointestinal lesions and their complications (gastric erosions, peptic ulcer disease, angiodysplasia, and gastrointestinal bleeding) [14] [15] [16]. H. pylori plays a major role in the genesis of many gastrointestinal conditions both in individuals with normal renal function and CKD.…”
Section: Introductionmentioning
confidence: 99%
“…pylori, a gram-negative bacterium, colonizes the human gastric mucus layer. Recently, considerable studies changed the paradigm that H. pylori only participates in the pathogenesis of chronic gastritis and peptic ulcer disease, and demonstrated that several extra-intestinal diseases, such as renal-related diseases, were also caused by H. pylori [6][7][8]. The systemic antibody response to H. pylori was reported to be increased in patients with IgAN [9], suggesting that H. pylori might be involved in the pathogenesis and progression of IgAN.…”
Section: Introductionmentioning
confidence: 99%